ANALISIS DAMPAK PROGRAM REVITALISASI PASAR TRADISIONAL DI PASAR TUMENGGUNGAN TERHADAP PENDAPATAN PEDAGANG DAN EVALUASI MANAJEMEN TATA KELOLA PEDAGANG PASAR TUMENGGUNGAN PASCA PROGRAM REVITALISASI MENURUT PERSEPSI PEDAGANG - Siti Nur Azizah (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2016)
The aim of this study is to analyze the income of the sellers on Tumenggungan market and evaluation of governance market traders post Tumenggungan revitalization program perception by traders. The data used are primary data, consisted of the sellers income before and after the market revitalization programm. The result of this research shows that the sellers income before and after the market revitalization programm are significanly different. Based on the survey results revealed all the indicators of input, process and output of the revitalization program Tumenggungan perceived market traders have increased. Therefore we can conclude the market revitalization program Tumenggungan a positive impact on revenue management and governance of the better post revitalization program Keywords : income, market revitalization